Epidemiologic Features of Kawasaki Disease in Japan: Results of the 2007–2008 Nationwide Survey - Yosikazu Nakamura; Mayumi Yashiro; Ritei Uehara; Atsuko Sadakane; Izumi Chihara; Yasuko Aoyama; Kazuhiko Kotani; Hiroshi Yanagawa (2010)
Background: The most recent epidemiologic features of Kawasaki disease (KD) are unknown.Methods: The 20th nationwide survey of KD was conducted in 2009, and included patients treated for the disease in 2007 and 2008. Hospitals specializing in pediatrics, and hospitals with pediatric departments and 100 or more beds, were asked to report all patients with KD during the 2 survey years.Results: From a total of 1540 departments and hospitals, 23 337 patients (11 581 in 2007 and 11 756 in 2008) were reported: 13 523 boys and 9814 girls. The annual incidence rates were 215.3 and 218.6 per 100 000 children aged 0–4 years in 2007 and 2008, respectively. These were the highest annual KD incidence rates ever recorded in Japan. The monthly number of patients peaked during the winter months; smaller increases were noted in the summer months. The age-specific incidence rate showed a monomodal distribution with a peak at age 9–11 months. The prevalences of both cardiac lesions during the acute phase of the disease and cardiac sequelae were higher among infants and older age groups.Conclusions: The incidence rate and number of patients with KD in Japan continue to increase.